Building Organizational Identity in Minority Communities - Pilotta, Joe (Sociologija. Mintis ir veiksmas, 2005)
The purpose of this article is to outline the basic methodological, theoretical, and technical issues in the development and practice of organizational identity formation through research. Power, or more precisely, empowerment is conceptualized as a proper communication variable rather than as a poorly disguised analogue of a dimension of physical calculation. This means that we shall not entertain in this discussion the push-pull metaphors so endemic to analyses presupposing the mechanical triad, force-resistance-change. Instead, we shall make some explicit assumptions about organizations and generate a communication evaluation of power.